Newsletters and flyers - Charalambous, Andreas; Moutsiou, Theodora; Agapiou, Athos; Kyriakidis, Phaedon; Lysandrou, Vasiliki (My University, 2018)
This deliverable (D4.3: Newsletters and flyers) presents the outreach material that was created and widely distributed during Phase I of the MedSTACH project. The list includes two electronic newsletters, a leaflet, a pamphlet and a roll up banner all developed by the Consortium and produced using the services of professional designers/printers. These outreach items were used as promotional material in order to provide progress updates on the MedSTACH’s activities and results and to provide information on future dissemination events planned by the project and the proposed Centre of Excellence. The roll up banner followed the Consortium in all its activities as an effective visual means of promoting the Project and encouraging questions/discussions by the respective audiences. The leaflet and pamphlet were circulated as promotional material of MedSTACH project at the various events – such as info days and international conferences – Consortium members participated in. Finally, the two e-newsletters were electronically distributed to members of the academic and industrial sectors and the numerous individuals who signed up as friends of MedSTACH during public events and/or the Project’s website.
D4.3 (Newsletters and flyers)
Keywords: Newsletters; Flyers; E-newsletters